Larvicidal and Anti-inflammatory Activities of Funtumia Africana (Benth) Stapf Leaf and Stem - ADEDIWURA Fred-JAIYESIMI; TOCHUKWU DUNKWU; OLUWANISOLA OKUROUNMU (International Journal of Phytomedicine, 2015)
Larvicidal and Anti-inflammatory Activities of Funtumia Africana (Benth) Stapf Leaf and Stem